Patrones ecológicos y genéticos de adaptación en los amerindios Guaymí de Costa Rica y Panamá - Barrantes, Ramiro (Revista de Biología Tropical, 1988)
Some anthropological and genetic features of the Guaymi Amerindian group of Costa Rica and Panama are described in an ecological context. The fission-fusion phenomenon and the lineal effect are present; however, there are some important differences in relation to other hunter gatherer indian groups. These adaptation patterns are important for the genetic structure and evolution of the Guaymi Amerindians in the Intermediate Zone.